Perspective asupra învățământului profesional și tehnic. Studiu de caz: Liceul Tehnologic Construcții de Maşini Mioveni - Mihalache, Flavius (Calitatea Vieții, 2016)
This paper presents the main results of a qualitative research on vocational education, conducted in a high school from Mioveni. The high school (LTCM) is one of the most important vocational schools in Arges county. For almost 50 years it offers secondary educational programs in various industrial fields. During the last decades the school has been permanently connected to the economic activities from the Mioveni micro-region, especially to DACIA industrial platform. The study explores the relationship between school and companies taking into account the specificity of the Mioveni micro-region. The research perspective is mainly descriptive. We are interested to explore how the school-firms cooperation is built and how this connection could evolve in the future. The major conclusion of the research reveals that vocational education represents more than an alternative to general education. It can be understand as an effective way to connect educational offer to the labour market demand. The cooperation between school and significant local companies, despite its weak points, has a great importance for improving educational programs. Significantly more research is needed, both to explore this situation and to guid the future educational policies.